Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Camille Beauty di Kalangan Mahasiswa UBP Karawang - Oktapiani, Shanti; Mulyadi, Dedi; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the effect of product quality on the purchasing decisions of Camille Beauty products among students at Universitas Buana Perjuangan (UBP) Karawang. Using a quantitative method and purposive sampling technique, the study involved 30 respondents who have purchased or used Camille Beauty products. The analysis results show that product quality has a significant effect on purchasing decisions. Data were collected through questionnaires and processed using validity tests, reliability tests, and simple linear regression analysis. The results of this study indicate that good product quality can enhance the purchasing decisions of UBP Karawang students regarding Camille Beauty products.